Millennial university students' valuation of traditional wine: Evidence from an experimental auction - Elói Jorge; Ernesto Lopez-Valeiras; Maria Beatriz Gonzalez-Sanchez (Wine Economics and Policy, 2021)
This paper analyzes whether the perception of traditional wine brings value to millennials. Based on survey data and experimental auctions (165 participants), this study identifies the main factors affecting this consumer groups' willingness to pay for traditional wine through a Tobit model methodology. The results suggest that millennials are willing to pay a higher price depending on demographic factors such as monthly disposable income, on wine involvement variables such as consumption frequency, and on nourishing and health aspects and product availability at points of sale, both of which are wine purchase decision criteria. The investigation has significant marketing and policy implications.
Keywords: 330; Traditional Wine; millennials; willingness to pay; purchase decision variables; experimental auction